2022
DOI: 10.1021/acs.orglett.2c01633
|View full text |Cite
|
Sign up to set email alerts
|

Unified Total Synthesis of Diverse Meroterpenoids from Ganoderma Applanatum

Abstract: A unified approach to meroterpenoids applanatumols B, V, W, X, and Y produced by the medicinal fungus Ganoderma applanatum and 2′-epi-spiroapplanatumine O is presented. The key synthetic sequence consists of a tandem anionic ketone allylation/oxy-Cope rearrangement/α-oxygenation furnishing an α-aminoxy ketone and a persistent radical effectbased 5-exo-trig cyclization leading to the trisubstituted cyclopentane core. The relative configuration of applanatumol V has to be revised. Some compounds display signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…29 Absolute configuration elucidations of these racemates were accomplished by ECD calculations and CD comparisons, and the relative configurations of (±)-applanatumol V (141 and 142) were revised by using synthesis methods. 66 Unusual enantiomers of (±)-applanatumol B (156 and 157) possessing a dioxacyclopenta[cd]inden motif were characterized by spectroscopic methods and ECD calculations. 67 In terms of biosynthetic pathway, the precursor of applanatumol B may be a derivative of applanatumol V (141 and 142) (Supporting Information: Scheme S1).…”
Section: F I G U R E 6 Structures Of Ganoderma Meroterpenoid Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…29 Absolute configuration elucidations of these racemates were accomplished by ECD calculations and CD comparisons, and the relative configurations of (±)-applanatumol V (141 and 142) were revised by using synthesis methods. 66 Unusual enantiomers of (±)-applanatumol B (156 and 157) possessing a dioxacyclopenta[cd]inden motif were characterized by spectroscopic methods and ECD calculations. 67 In terms of biosynthetic pathway, the precursor of applanatumol B may be a derivative of applanatumol V (141 and 142) (Supporting Information: Scheme S1).…”
Section: F I G U R E 6 Structures Of Ganoderma Meroterpenoid Alkaloidsmentioning
confidence: 99%
“…136 And in 2022, the Jahn group achieved applanatumols B, X and Y in 13 and 10 steps, respectively, and reported the first total syntheses of applanatumol V (141) in 10 steps and applanatumol W (143) in 11 steps. 66 The Qin and Liu group described the first total synthesis of (±)-cochlearol A (164 and 165) in 16 steps, relying on a TMSOTf-catalyzed lactonization of tert-butyl ether and ethyl ester. 137 Later, in 2020, Ishigami et al reported their syntheses approach of (±)-cochlearol A (164 and 165) via an intramolecular acetal reaction of a key spiroepoxide intermediate.…”
Section: The Total Synthesis Of Gmsmentioning
confidence: 99%
See 2 more Smart Citations
“…1366 Applying this strategy, interesting scaffolds could be constructed, and applications in the total synthesis of diverse meroterpenoids were presented (Scheme 89a). 1367 For example, with tetraallyltin, an allyl group was added to the dienone 291, and warming of the reaction mixture induced an oxy-Cope rearrangement of intermediate 292 to give a keto enolate, which was SET oxidized and trapped by TEMPO to give the alkoxyamine 293. Under reflux condition, alkoxyamine isomerization comprising a 5-exo-cyclization was achieved to give 294.…”
Section: Reactions Of Alkoxyaminesmentioning
confidence: 99%